Promotion of Adventitious Root Formation of Miracle Fruit (Synsepalum dulcificum Daniell) Through Stem Cuttings and Air Layering Technique - Rozalia, Mohd Geoffery; Hamsawi, Sani (Transactions on Science and Technology, 2017)
Synsepalum dulcificum or Miracle fruit plant is a medicinal shrub that belongs to the family Sapotaceace are known to exert an extraordinary effect of changing sour taste to sweet. The increase in industrial demand may cause depletion on the raw materials source as it is a slow-growing plant. Propagations of miracle fruits are restricted due to difficulties in rooting through cuttings and the seeds are recalcitrant. This study was to overcome the needs to supply large number of seedlings for large-scale planting by inducing adventitious root formation through vegetative propagation methods such as stem cutting and air layering (marcotting). A total of 140 softwood stem cuttings were treated with four IBA concentrations (0, 500, 1000, and 2000 mg/L) and planted in sand bed under non-mist system. Another experiment involved air layering was initiated on vertical young shoots treated with commercial rooting hormone Seradix No.2 (3000 ppm). Percentages of rooting (%), mean number of root (%), and mean root length (cm) per rooted cutting were collected 2 months after planting. Stem cuttings soaked in control treatment produced the highest percentage of rooting (54.28%) per cutting. However, mean root numbers per rooted cutting increases with high concentrations of IBA treatment. Adventitious root started to emerge four weeks after propagation period in air layering method. Results showed that 73.33% air layers successfully induced roots with mean root length 5.98cm. Thus, vegetative propagation is a promising technique that can be applied to promote adventitious rooting in hard-to-root species as in Synsepalum dulcificum.